Cross Modulation between the Androgen Receptor Axis and Protocadherin-PC in Mediating Neuroendocrine Transdifferentiation and Therapeutic Resistance of Prostate Cancer - Terry, Stéphane (Neoplasia Press Inc., 2013)
Castration-resistant prostate cancers (CRPCs) that relapse after androgen deprivation therapies (ADTs) are responsible for the majority of mortalities from prostate cancer (PCa). While mechanisms enabling recurrent activity of androgen receptor (AR) are certainly involved in the development of CRPC, there may be factors that contribute to the process including acquired neuroendocrine (NE) cell-like behaviors working through alternate (non-AR) cell signaling systems or AR-dependent mechanisms. In this study, we explore the potential relationship between the AR axis and a novel putative marker of NE differentiation, the human male protocadherin-PC (PCDH-PC), in vitro and in human situations. We found evidence for an NE transdifferentiation process and PCDH-PC expression as an early-onset adaptive mechanism following ADT and elucidate AR as a key regulator of PCDH-PC expression. PCDH-PC overexpression, in turn, attenuates the ligand-dependent activity of the AR, enabling certain prostate tumor clones to assume a more NE phenotype and promoting their survival under diverse stress conditions. Acquisition of an NE phenotype by PCa cells positively correlated with resistance to cytotoxic agents including docetaxel, a taxane chemotherapy approved for the treatment of patients with metastatic CRPC. Furthermore, knockdown of PCDH-PC in cells that have undergone an NE transdifferentiation partially sensitized cells to docetaxel. Together, these results reveal a reciprocal regulation between the AR axis and PCDH-PC signals, observed both in vitro and in vivo, with potential implications in coordinating NE transdifferentiation processes and progression of PCa toward hormonal and chemoresistance.